Obstetric Management in Maternal with COVID-19: A Narrative Literature Review - Giovano, Asoly (HM Publisher, 2021)
The incidence of COVID-19 in pregnant women varies by geographic region and population. However, pregnant women may be at an increased risk of COVID-19 infection compared to non-pregnant women. Several risk factors have been identified for severe COVID-19 illness in pregnant women, including maternal age, obesity, chronic medical conditions, ethnicity, gestational age, and multiple pregnancies. Screening and testing for COVID-19 in pregnant women is essential to prevent transmission and ensure appropriate management. Pregnant women should be screened for symptoms at each prenatal visit, and those with symptoms or high-risk exposures should be tested using a PCR-based assay. Repeat testing may be necessary in certain situations, and universal testing may be implemented in some healthcare facilities. Antibody testing is not currently recommended for diagnosis or management of pregnant women. The delivery management of pregnant women with COVID-19 should be individualized based on the severity of the illness, gestational age, and fetal status. The neonatal management of infants born to mothers with COVID-19 should focus on the prevention of transmission and optimization of neonatal outcomes. Neonates should be evaluated for COVID-19 using a PCR-based assay, and respiratory support should be provided.